Secondary battery, battery module, battery pack and power consuming device

By employing solid electrolytes with controlled polymer fractions and additives, the secondary battery achieves improved safety, cycle, and power performance by stabilizing the electrolyte interface, addressing the limitations of liquid electrolytes.

JP2025502253AActive Publication Date: 2025-01-24CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024541953
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-01-24
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in balancing safety performance, cycle performance, and power performance, particularly due to the limitations of liquid electrolytes, which can lead to safety issues and reduced efficiency.

Method used

The use of solid electrolytes with a polymer mass fraction and specific additives on the surface of electrode layers, forming a stable SEI membrane, combined with a controlled ratio of polymer mass tricks and additives, enhances the adhesion and stability of the electrolytes, reducing impedance and improving the cycle and power performance.

Benefits of technology

This approach results in improved cycle stability, reduced internal resistance, and enhanced power performance by stabilizing the electrolyte interface, thereby increasing the safety and efficiency of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502253000001_ABST
    Figure 2025502253000001_ABST
Patent Text Reader

Abstract

The present application provides a secondary battery, a battery module, a battery pack, and a power consumption device. The secondary battery includes a positive electrode sheet including a positive electrode film layer, a negative electrode sheet including a negative electrode film layer, an electrolytic solution, and a solid electrolyte, the solid electrolyte is provided on the surface of the positive electrode film layer and / or the negative electrode film layer and includes a polymer matrix and a first additive, the first additive is arranged to form an interfacial film on the surface of the positive electrode film layer and / or the negative electrode film layer, where the mass percentage of the polymer matrix relative to the total mass of the solid electrolyte is A%, the mass percentage of the first additive relative to the total mass of the solid electrolyte is B%, and the secondary battery satisfies 0.1≦B / A≦19. The present application uses a combination of a solid electrolyte and a liquid electrolyte to achieve both the advantages of the solid electrolyte and the advantages of the liquid electrolyte, and improves the dynamic performance, safety performance, and cycle performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]

[0002] Due to their characteristics of high capacity and long life, secondary batteries are widely used in electronic devices, such as mobile phones, notebook computers, electric bicycles, electric cars, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, electric tools, etc. As the range of applications of batteries becomes wider and wider, the requirements for the performance of secondary batteries become more and more stringent.

[0003] However, when improving the performance of a secondary battery, it is difficult to simultaneously achieve the safety performance, cycle performance, and dynamic performance of the secondary battery. Summary of the Invention

[0004] The present application has been made in view of the above-mentioned problems, and has an object to provide a secondary battery, a battery module, a battery pack, and a power consuming device.

[0005] A first aspect of the present application provides a secondary battery, the secondary battery including a positive electrode sheet including a positive electrode membrane layer, a negative electrode sheet including a negative electrode membrane layer, an electrolytic solution, and a solid electrolyte, the solid electrolyte being provided on a surface of the positive electrode membrane layer and / or the negative electrode membrane layer and including a polymer matrix and a first additive, the first additive being arranged to form an interfacial film on the surface of the positive electrode membrane layer and / or the negative electrode membrane layer, wherein a mass percentage of the polymer matrix relative to a total mass of the solid electrolyte is A%, and a mass percentage of the first additive relative to a total mass of the solid electrolyte is B%, and the secondary battery satisfies 0.1≦B / A≦19, and preferably 0.5≦B / A≦10.

[0006] Thus, the polymer matrix in the solid electrolyte of the present application has a certain adhesiveness, and allows the solid electrolyte to adhere to the surface of the active material. The solid electrolyte has excellent thermal stability and chemical stability, and can maintain good cycle stability during the charge and discharge process of the secondary battery, and can improve the cycle performance of the secondary battery. The solid electrolyte has a wider stable electrochemical window, and the wider stable electrochemical window ensures that the electrolyte and the positive and negative electrodes are less likely to undergo bad interface reactions during the charge and discharge process, so that the internal resistance of the secondary battery can be reduced, heat generation can be reduced, and the safety performance and service life of the secondary battery can be improved. In addition, the first additive forms an interface film on the active material surface that is not too thick, which is favorable for the transmission of metal ions, and the impedance of the interface film is low, which is favorable for improving the dynamic performance of the secondary battery. The combination of the solid electrolyte and the liquid electrolyte can be used to achieve both the advantages of the solid electrolyte and the liquid electrolyte, and improve the dynamic performance, safety performance, and cycle performance of the secondary battery.

[0007] In any embodiment, the secondary battery satisfies 5≦A≦99 and / or 0.1≦B≦95. When the mass percentage of the polymer matrix is ​​within the above range, the adhesion between the polymer matrix and the active material can be ensured, and the solid electrolyte is not easily detached from the surface of the active material during the charge and discharge process of the secondary battery. When the mass percentage of the first additive is within the above range, the first additive forms a uniform and stable interface film in the positive electrode film layer and / or the negative electrode film layer, and the impedance of the interface film is relatively low, which is favorable for improving the dynamic performance of the secondary battery.

[0008] In any embodiment, the first additive includes a boron-containing lithium salt having a mass percentage of B1% relative to the total mass of the solid electrolyte, and an anode film-forming additive having a mass percentage of B2% relative to the total mass of the solid electrolyte, where the secondary battery satisfies 0.002≦B1 / B2≦10. When the mass percentage of the anode film-forming additive of the present application is within the above range, it is ensured that both the anode film-forming additive and the boron-containing lithium salt form a uniform and stable SEI film, and the protective performance for the anode active material can be further improved.

[0009] In any embodiment, the secondary battery satisfies 0.1≦B1≦50 and / or 0.1≦B2≦50.

[0010] In any embodiment, the boron-containing lithium salt has the molecular formula LiBF a O b C c P d In the molecular formula, 0≦a≦4, 0≦b≦8, 0≦c≦4, and 0≦d≦4. Preferably, the boron-containing lithium salt includes one or more of lithium tetrafluoroborate LiBF4, lithium bis(oxalato)borate LiBOB, and lithium bis(fluorooxalato)borate LiDFOB.

[0011] As a result, the lithium tetrafluoroborate LiBF4, lithium bis(oxalato)borate LiBOB and lithium bis(fluorooxalato)borate LiDFOB of the present application are mixed and used, and the SEI film formed by the three has many components, and the structure of the SEI film is more stable. In addition, after ensuring the stable structure, the impedance value of the SEI film is relatively small, and the low-temperature performance of the secondary battery can be ensured.

[0012] In any embodiment, the negative electrode film-forming additive comprises one or more of carbonate-based additives, sulfate-based additives and sulfite-based additives. The negative electrode film-forming additive and the boron-containing lithium salt of the present application are mixed together to form an SEI film on the surface of the negative electrode active material, and the components are mixed together to form a film on the surface of the SEI film, thereby enriching the film layer structure of the SEI film and improving the structural stability of the SEI film.

[0013] In any embodiment, the carbonate ester-based additive includes a cyclic carbonate ester solvent and / or a chain carbonate ester solvent, and preferably, the cyclic carbonate ester solvent includes one or more of vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinylethylene carbonate VEC, and dioctyl carbonate CC, and the chain carbonate ester solvent includes one or more of ethyl allyl carbonate AEC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA, and and / or the sulfate-based additive comprises a cyclic sulfonate-based additive and / or a hydrocarbon-based sulfate-based additive, preferably the cyclic sulfonate-based additive comprises one or more of 1,3-propane sultone PS, propene sultone PES, 3-fluoro-1,3-propane sultone FPS, and / or the hydrocarbon-based sulfate-based additive comprises one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS, and / or the sulfite-based additive comprises ethylene sulfite ES and / or vinyl ethylene sulfite VES.

[0014] In any embodiment, the electrolyte solution contains a cyclic carbonate ester solvent having a mass percentage of M1% relative to the total mass of the electrolyte solution, and a chain carbonate ester solvent having a mass percentage of M2% relative to the total mass of the electrolyte solution, -3 ≦M1 / M2≦2, preferably 0.1≦M1 / M2≦1, more preferably 1≦M1≦20, and / or 50≦M2≦85. When the mass percentages of the cyclic carbonate ester solvent and the chain carbonate ester solvent of the present application are within the above ranges, the ionic conductivity of the electrolyte can be further improved.

[0015] In any embodiment, the cyclic carbonate ester solvent comprises one or more of ethylene carbonate EC, propylene carbonate PC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC, and / or the linear carbonate ester solvent comprises one or more of ethyl allyl carbonate AEC, diphenyl carbonate DPC, and methyl allyl carbonate MAC, polycarbonate VA, diethyl carbonate DEC, ethyl methyl carbonate EMC, methyl propyl carbonate MPC, ethyl propyl carbonate EPC, methyl butyl carbonate MBC, methyl acetate MA, ethyl acetate EA, methyl propionate MP, and ethyl propionate EP.

[0016] In any embodiment, the electrolyte solution includes an electrolyte film-forming additive having a mass percentage of D1% relative to the total mass of the electrolyte solution, and a lithium salt having a mass percentage of D2% relative to the total mass of the electrolyte solution, and the secondary battery satisfies 0.2≦E / (D1+D2)≦2.95, where E represents the viscosity of the electrolyte solution and is expressed in mPa s.

[0017] When the secondary battery satisfies the above formula, it is favorable for improving the dynamic performance of the electrolyte. For example, when a relatively high content of lithium salt and electrolyte film-forming additive is added, the viscosity of the electrolyte is increased, which is favorable for cooperation between the electrolyte and the solid electrolyte, and the electrolyte film-forming additive is more likely to form a film on the active material surface through the solid electrolyte. When a chain carbonate ester solvent is added to the electrolyte, the viscosity of the electrolyte can be further controlled to be in a low range, which is favorable for the movement of lithium ions and ensures the dynamic performance of the electrolyte.

[0018] In any one of the embodiments, the percentage of the solid mass content of the solid electrolyte solution relative to the liquid mass content is m, and the compressed density of the positive electrode membrane layer is P1 g / cm 3 The thickness of the positive electrode film layer is h1 μm, and the secondary battery is 5≦h1 *P1 / m≦250 is satisfied. When the secondary battery of the present application satisfies the above range, the polymer slurry can provide good coverage for the active material and provide interface protection. In this limited relationship, the diffusion path of the polymer slurry is appropriate, matches the viscosity of the polymer slurry, and is favorable for the polymer slurry to diffuse into the active material, and matches the appropriate compressed density, so that the porosity of the positive electrode membrane layer is appropriate and is favorable for the polymer slurry to diffuse into the voids of the active material, thereby strengthening the degree of bonding between the solid electrolyte and the active material formed by the polymer slurry, and making the impedance of the interface between the solid electrolyte and the active material relatively low.

[0019] In any one of the embodiments, the percentage of the solid mass content of the solid electrolyte solution relative to the liquid mass content is m, and the compressed density of the negative electrode membrane layer is Pg / cm 3 The thickness of the negative electrode film layer is h2μm, and the secondary battery is 25≦h2 * P2 / m≦245 is satisfied. When the secondary battery of the present application satisfies the above range, the polymer slurry has a good coating on the active material, the diffusion path of the polymer slurry is appropriate, the viscosity of the polymer slurry is suitable, and the polymer slurry is favorable for diffusion into the active material, and the compression density is suitable, so that the porosity of the negative electrode film layer is appropriate, and the polymer slurry is favorable for diffusion into the voids of the active material, and thus the degree of bonding between the solid electrolyte formed by the polymer slurry and the active material is strong, and the impedance of the interface between the solid electrolyte and the active material is relatively low.

[0020] A second aspect of the present application further provides a battery module including a secondary battery according to any one of the embodiments of the first aspect of the present application.

[0021] A third aspect of the present application further provides a battery pack including a battery module according to an embodiment of the second aspect of the present application.

[0022] A fourth aspect of the present application further provides a power consuming device comprising a secondary battery according to any of the embodiments of the first aspect of the present application, a battery module according to an embodiment of the second aspect of the present application, or a battery pack according to an embodiment of the third aspect of the present application. [Brief description of the drawings]

[0023] In order to more clearly describe the technical solutions of the embodiments of the present application, the drawings necessary for the embodiments of the present application are briefly described below. It is clear that the drawings described below are only some embodiments of the present application. Those skilled in the art can further obtain other drawings based on the drawings even without creative labor.

[0024] [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a secondary battery of the present application. [Diagram 2] FIG. 2 is an exploded schematic view of the embodiment of the secondary battery of FIG. 1. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Diagram 5] 5 is an exploded schematic view of the embodiment of the battery pack shown in FIG. 4. [Figure 6] 1 is a schematic diagram of one embodiment of a power consuming device that includes a secondary battery of the present application as a power source. The drawings are not necessarily drawn to scale.

[0025] Explanation of symbols 1, battery pack; 2, upper housing; 3, lower housing; 4, battery module; 5, secondary battery; 51, case; 52, electrode assembly; 53, cover plate; 6, power consumption device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, the embodiments specifically disclosing the secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of known matters or duplicate description of substantially the same configuration may be omitted. This is to avoid unnecessary redundancy in the following description and to facilitate understanding by those skilled in the art. Note that the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0027] The "ranges" disclosed in this application are defined in the form of lower and upper limits, where a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, when ranges of 60-120 and 80-110 are recited for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, when minimum range values ​​1 and 2 and maximum range values ​​3, 4 and 5 are recited, ranges of 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 may all be contemplated. In this application, unless otherwise stated, the numerical range "a-b" is represented by the abbreviation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" are listed herein, with "0-5" being an abbreviation for combinations of these numerical values. Furthermore, expressing a parameter as an integer greater than or equal to 2 (≧2) is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0028] Unless otherwise specified, all the embodiments and optional embodiments of the present application may be combined with each other to form a new technical solution, and such technical solution is considered to be included in the disclosure content of the present application.

[0029] Unless otherwise stated, all steps in the present application may be performed in sequence or randomly, but are preferably performed in sequence. For example, the method includes steps (a) and (b) and may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, when it is stated that the method may further include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0030] Unless otherwise specified, the terms "comprise" and "include" used in this application mean open-ended and may also be closed-ended. For example, the terms "comprise" and "include" can mean "comprise" or "include" other components not listed, or "comprise" or "include" only the listed components.

[0031] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions are met: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).

[0032] In this application, the terms "plurality" and "plurality" mean two or more than two.

[0033] Secondary batteries are widely used due to their characteristics such as high capacity and long life. With the development of the new energy industry, higher requirements have been put forward for the electrical performance and reliability of secondary batteries. Although the energy density and battery capacity of secondary batteries have improved, secondary batteries may have safety problems. For example, during the charging and discharging process of a high-capacity secondary battery, the separator may be destroyed by heat accumulated inside the secondary battery, causing the cathode and anode to come into contact with each other, which may cause phenomena such as combustion due to a rapid oxidation-reduction reaction. Due to the safety issues of the liquid electrolyte itself, the development of secondary batteries is limited, and it is important to develop secondary batteries with higher safety.

[0034] Based on this, the inventors have found that the surface of the electrode sheet is coated with a solid electrolyte for protection, and the solid electrolyte has higher thermal and chemical stability than a liquid electrolyte, and since the solid electrolyte is provided on the surface of the electrode sheet, even if the separator is damaged, the cathode and anode cannot be prevented from directly contacting each other, and therefore high safety is ensured. Secondly, the solid electrolyte has a wide electrochemical window, which effectively reduces the generation of interfacial side reactions, improves the cycle life of the secondary battery, and also provides good electrochemical stability and can match a positive electrode active material with a higher charging voltage, resulting in a high energy density. However, the interface between the solid electrolyte and the active material is a solid-solid interface, and the effective contact between the solid electrolyte and the active material is weak, resulting in low kinetics of transport of metal ions in the solid material, and therefore the impedance of the interface is large.

[0035] Therefore, the inventors have conducted extensive research into secondary batteries and found that by using a combination of a solid electrolyte and an electrolytic solution, a specific substance can be added to the solid electrolyte to improve the protection performance of the active material, and the impedance between the solid electrolyte and the active material can be reduced to improve the dynamic performance, and an electrolytic solution with a relatively low viscosity can be combined to improve the dynamic performance of the electrolytic solution, thereby comprehensively improving the dynamic performance, safety performance, and cycle performance of the secondary battery. Next, the technical solution of this application will be described in detail.

[0036] secondary battery

[0037] According to a first aspect, the present application provides a secondary battery, also called a rechargeable battery or storage battery, which is a battery that can be continuously used by activating the active material by charging after discharging the battery.

[0038] The secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolytic solution, and a solid electrolyte, the positive electrode sheet includes a positive electrode film layer, the negative electrode sheet includes a negative electrode film layer, a solid electrolyte is provided on at least one surface of the positive electrode film layer and the negative electrode film layer, the solid electrolyte includes a polymer matrix and a first additive, the first additive is arranged to form an interface film on a surface of the positive electrode film layer and / or the negative electrode film layer, wherein a mass percentage of the polymer matrix with respect to a total mass of the solid electrolyte is A%, a mass percentage of the first additive with respect to a total mass of the solid electrolyte is B%, and the secondary battery satisfies 0.5≦B / A≦19.

[0039] Although the mechanism is not clear, the secondary battery of the present application can comprehensively improve the dynamic performance, safety performance and cycle performance of the secondary battery.

[0040] The inventors speculate that the mechanism of action of the present invention is as follows.

[0041] The solid electrolyte may be provided on the positive electrode membrane layer, and the positive electrode membrane layer includes a positive electrode active material, i.e., the solid electrolyte is provided on the positive electrode active material, and the first additive in the solid electrolyte and the positive electrode active material can undergo a film-forming reaction, and a CEI film, which is a positive electrode solid electrolyte interphase film, can be formed on the surface of the positive electrode active material. The solid electrolyte may be provided on the negative electrode membrane layer, and the solid electrolyte is provided on the negative electrode active material, and the first additive in the solid electrolyte and the negative electrode active material can undergo a film-forming reaction, and a solid electrolyte interphase film (Solid Electrolyte Interphase, SEI film) is formed on the surface of the negative electrode active material. Alternatively, the solid electrolyte may be provided on the positive electrode membrane layer and the negative electrode membrane layer, and the solid electrolyte is provided on the positive electrode active material and the negative electrode active material. In this application, the CEI film and the SEI film are collectively referred to as interphase films.

[0042] The solid electrolyte is provided on the active material, and the polymer matrix in the solid electrolyte has a certain adhesiveness, so that the solid electrolyte is attached to the surface of the active material. The solid electrolyte has excellent thermal stability and chemical stability, and can maintain good cycle stability during the charge and discharge process of the secondary battery, and can improve the cycle performance of the secondary battery. The solid electrolyte has a wider stable electrochemical window, and the wider stable electrochemical window ensures that the electrolyte and the positive and negative electrodes are less likely to undergo bad interfacial reactions during the charge and discharge process, so that the internal resistance of the secondary battery can be reduced, heat generation can be reduced, and the safety performance and service life of the secondary battery can be improved.

[0043] The polymer matrix generally has a porous structure, and the pore size is small. When the first additive and the polymer matrix form a solid electrolyte, the first additive fills the pores of the polymer matrix, the first additive is uniformly dispersed in the polymer matrix, and the groups in the polymer matrix form a complex coordination action with the metal ions in the first additive, such as lithium ions, and the metal ions repeat the coordination and dissociation action on the polymer matrix along with the irregular Brownian motion process of the polymer matrix, thereby realizing the transmission of lithium ions. Since the first additive used for film formation is provided in the solid electrolyte, the amount of the first additive used is small, and the water content due to the introduction of the first additive can be reduced, thereby reducing the risk of side reactions inside the secondary battery.

[0044] After the electrolyte is injected into the secondary battery, the electrolyte infiltrates the positive and negative electrode sheets, and when the solid electrolyte is infiltrated with the electrolyte, the first additive contained therein dissolves in the electrolyte, and the dissolved first additive is more likely to form an interface film on the surface of the active material, which provides good protection for the active material, and the interface film formed on the active material surface by the first additive is not too thick, which is favorable for the transport of metal ions, and the impedance of the interface film is low, which is favorable for improving the dynamic performance of the secondary battery. In addition, the solid electrolyte can reduce the risk of side reactions caused by contact between the solvent in the electrolyte and the positive and negative electrode sheets, and can also reduce the possibility of decomposition of the electrolyte.

[0045] In the charging process of the secondary battery, the metal ion is lithium ion as an example, and the kinetic process generally includes the steps of lithium ion being desorbed from the positive electrode active material and moving to the electrolyte phase, solvated lithium ion in the electrolyte solution being diffused and transferred to the surface of the negative electrode active material, and lithium ion obtaining electrons from the surface of the negative electrode active material and diffusing into the inside of the negative electrode active material. In the process of lithium ion being desorbed from the positive electrode active material to the electrolyte phase, the CEI film on the surface of the positive electrode active material is thin and its migration barrier is relatively low, and the electrolyte solution is a liquid electrolyte with a relatively low viscosity and high ionic conductivity, so that in the process of lithium ion migration from the electrolyte solution to the negative electrode active material, its migration barrier is relatively low, and the SEI film on the surface of the negative electrode active material is thin and the migration barrier of lithium ion migration from the SEI film to the inside of the negative electrode active material is also relatively low, so that the migration barrier in the entire kinetic process of lithium ion is low, the required energy is small, and it is favorable for the rapid migration of lithium ion, and the kinetic performance of the secondary battery is relatively good.

[0046] The present application uses a combination of a solid electrolyte and a liquid electrolyte to achieve both the advantages of a solid electrolyte and a liquid electrolyte, thereby improving the dynamic performance, safety performance, and cycle performance of a secondary battery.

[0047] [Solid electrolyte]

[0048] The solid electrolyte includes a polymer matrix and a first additive. In some embodiments, the polymer matrix includes one or more of polyethylene oxide PEO, polyurethane PU, polymethyl methacrylate PMMA, polyacrylonitrile PAN, polyvinylidene fluoride PVDF, poly(vinylidene fluoride-hexafluoropropylene) P(VDF-HFP), polypropylene carbonate PPC and polycarbonate PC, polyvinyl chloride PVC, polyethylene carbonate PEC, polylactic acid PLA, polytetrafluoroethylene PTFE, and characteristic functional group-containing blends and copolymers, the characteristic functional group includes an electron-withdrawing group, and illustratively, the electron-withdrawing group includes one or more of polymer polymers having polar atoms or polar groups such as fluorine atom F, nitrogen atom N, sulfur atom S, carbonyl -C=O, nitrile group -CN, and sulfonyl -S=O.

[0049] Blends are used to adjust the physical and chemical properties of materials, and include various blend systems such as PVDF-HFP / polyethyl methacrylate (PEMA), PEO / PVDF, PVDF-HFP / polyvinyl acetate (PVAc), PVC / PMMA, PVDF-HFP / PMMA, and PVDF-HFP / PAN, and copolymer systems include PEO-polystyrene (PSt), polydimethylsiloxane (PDMS)-PEO, PEGMA-MMA-IBVE, PEO-PMMA, POEM-PBMA, PPG-PEG-PPG, and MMA-AN-BA.

[0050] The polymer matrix has good mechanical properties, and the formed solid electrolyte has good flexibility, and can form a stable and good electrode-electrolyte interface with the active material. In addition, the molecular chain segments of the polymer matrix polymer have the ability of thermal motion, and the thermal motion of the molecular segments becomes intense with increasing temperature, and the polymer matrix has the ability of conducting lithium ions, which is favorable for metal ions, such as lithium ions, to constantly undergo a process of coordination-dissociation-coordination with characteristic atoms and groups, thereby realizing the transport of lithium ions within or between molecular chains of the polymer matrix, and the formed solid electrolyte has high ionic conductivity.

[0051] In some embodiments, the mass percentage A% of the polymer matrix is ​​5≦A≦99 with respect to the total mass of the solid electrolyte. When the mass percentage of the polymer matrix is ​​in the above range, the adhesion between the polymer matrix and the active material can be ensured, and the solid electrolyte is less likely to fall off from the surface of the active material during the charge and discharge process of the secondary battery. Preferably, 5≦A≦70. Exemplarily, the mass percentage A% of the polymer matrix may be 5%, 10%, 15%, 25%, 35%, 45%, 55%, 65%, 70%, 90%, 95% or 99%, or may be a range consisting of any two of the above values.

[0052] In some embodiments, the first additive may be used to form an interfacial film on the surface of the positive electrode membrane layer and / or the negative electrode membrane layer, and the mass percentage B% of the first additive is 0.1≦B≦95 with respect to the total mass of the solid electrolyte.

[0053] When the mass percentage of the first additive is in the above range, the first additive forms a uniform and stable interface film in the positive electrode film layer and / or the negative electrode film layer, and the impedance of the interface film is relatively low, which is advantageous for improving the dynamic performance of the secondary battery. Preferably, 10≦B≦95. Exemplarily, the mass percentage B% of the first additive may be 0.1%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 95%, or may be a range consisting of any two of the above values.

[0054] In some embodiments, the first additive may include a conductive lithium salt to ensure smooth movement of lithium ions. The conductive lithium salt may be selected as a boron-containing lithium salt. The boron-containing lithium salt has good compatibility with the polymer matrix, and the addition of the boron-containing lithium salt can reduce the glass transition temperature of the polymer matrix to a certain extent, and improve the mechanical strength and the stable temperature of the amorphous phase of the polymer matrix. The boron-containing lithium salt has a large anion group and is easy to dissociate lithium ions, so that the solubility of lithium ions is ensured and the ionic conductivity of the polymer electrolyte is improved.

[0055] In some embodiments, the molecular formula of the boron-containing lithium salt is LiBF a O b C c P d and in the molecular formula, 0≦a≦4, 0≦b≦8, 0≦c≦4, and 0≦d≦4.

[0056] The B atom can be bonded with an oxalic acid ligand containing oxygen. The product after bonding has excellent thermal stability and is easy to form a high-performance SEI film on the surface of the negative electrode active material, so that the structural stability of the negative electrode active material can be ensured and the cycle performance of the secondary battery can be improved. Of course, the B atom can be bonded with a halogen atom, especially a fluorine atom. The fluorine atom has a strong electron-attracting induction effect and has high thermal and chemical stability. In addition, the solubility of lithium ions in the electrolyte is high, which can ensure the solubility of lithium ions and ensure the conductivity of the electrolyte.

[0057] For example, the boron-containing lithium salt includes one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiB(C2O4)2, abbreviated as LiBOB), and lithium bis(fluorooxalato)borate (LiBC2O4F2, abbreviated as LiDFOB). Further, the boron-containing lithium salt includes a composition of lithium tetrafluoroborate LiBF4, lithium bis(oxalato)borate (LiB(C2O4)2, abbreviated as LiBOB), and lithium bis(fluorooxalato)borate (LiBC2O4F2, abbreviated as LiDFOB).

[0058] When lithium tetrafluoroborate (LiBF4) is used in combination with an organic solvent in an electrolyte, such as a carbonate-based solvent or an additive, the viscosity of the system made of lithium tetrafluoroborate is relatively low, which is favorable for the release of lithium ions, thereby improving the electrical conductivity of the electrolyte. The SEI film formed by lithium tetrafluoroborate has a uniform thickness, good kinetic activity, and small charge transfer resistance in a secondary battery, thereby significantly improving the low-temperature performance of the secondary battery. The SEI film is not easily thermally decomposed, and its performance at high temperatures is stable, thereby significantly improving the high-temperature performance of the secondary battery.

[0059] Either lithium bis(oxalate) borate LiBOB or lithium bis(fluorooxalate) borate LiDFOB has a passivation effect on the positive electrode current collector in the positive electrode sheet, and can reduce the risk of corroding the positive electrode current collector by a side reaction with the positive electrode current collector, and can improve the structural stability of the positive electrode sheet. In addition, an electrolyte containing either lithium bis(oxalate) borate LiBOB or lithium bis(fluorooxalate) borate LiDFOB is less likely to generate acidic substances, and can further reduce the risk of corroding the positive electrode current collector. Lithium bis(oxalate) borate LiBOB and lithium bis(fluorooxalate) borate LiDFOB have good compatibility with the positive electrode active material, are favorable for the movement of lithium ions, and can form an effective SEI film on the surface of the negative electrode active material, thereby improving the protective performance for the negative electrode active material.

[0060] By using lithium tetrafluoroborate LiBF4, lithium bis(oxalato)borate LiBOB, and lithium bis(fluorooxalato)borate LiDFOB in combination, the SEI film formed by the three has many components, and the structure of the SEI film is more stable. In addition, after ensuring the stability of the structure, the impedance value of the SEI film is relatively small, and the low-temperature performance of the secondary battery can be ensured.

[0061] In some embodiments, the mass percentage of the boron-containing lithium salt is B1%, relative to the total mass of the solid electrolyte, where 0.1≦B1≦50.

[0062] When the mass percentage of the boron-containing lithium salt is within the above range, the ion conduction ability of the solid electrolyte can be ensured. In addition, the positive electrode current collector can be well protected, and the negative electrode active material can be well protected. For example, the mass percentage B1% of the boron-containing lithium salt can be 0.1%, 0.5%, 1%, 2%, 10%, 20%, 25%, or 50%, etc.

[0063] In some embodiments, the conductive lithium salt may further include an ionically conductive lithium salt, which may include one or more of lithium hexafluoroarsenate LiPF6, lithium difluorophosphate LiPO2F2, difluorobisoxalate phosphate LiDODFP, lithium tetrafluorooxalate phosphate LiDFBP, lithium bisfluorosulfonyl imide LiFSI, lithium bistrifluoromethanesulfonyl imide LiTFSI, lithium fluorosulfonate LiSO3F, lithium nitrate LiNO3, lithium perchlorate LiClO4, lithium hexafluoroantimonate LiSbF6, and lithium hexafluoroarsenate LiAsF6. The ionically conductive lithium salt has a relatively high degree of dissociation and a high conductivity, which is favorable for the movement of lithium ions.

[0064] In some embodiments, the first additive may include a negative electrode film-forming additive. The negative electrode film-forming additive may include one or more of a carbonate-based additive, a sulfate-based additive, and a sulfite-based additive.

[0065] The negative electrode film-forming additive and the boron-containing lithium salt cooperate to form an SEI film on the surface of the negative electrode active material, and a plurality of components are formed on the surface of the SEI film together to enrich the film layer structure of the SEI film and improve the structural stability of the SEI film. In addition, the negative electrode film-forming additive includes at least two of carbonate ester-based additives, sulfate ester-based additives, sulfite ester-based additives and lithium fluorooxalate phosphate, and the SEI film formed therefrom has a rich composition and is more stable in structure.

[0066] The mass percentage of the negative electrode film-forming additive relative to the total mass of the solid electrolyte is B2%, where 0.1≦B2≦50.

[0067] When the mass percentage of the negative electrode film-forming additive is within the above range, the negative electrode film-forming additive can ensure that the negative electrode film-forming additive forms a uniform and stable SEI film, and can further improve the protection performance for the negative electrode active material. For example, the mass percentage B2% of the negative electrode film-forming additive can be 0.1%, 0.5%, 1%, 2%, 10%, 20%, 25%, or 50%, etc.

[0068] In some embodiments, 0.002≦B1 / B2≦9.

[0069] When the mass percentage of the negative electrode film-forming additive is within the above range, the negative electrode film-forming additive and the boron-containing lithium salt can form a uniform and stable SEI film, and can further improve the protection performance of the negative electrode active material. For example, B1 / B2 can be 0.002, 0.2, 0.5, 1, 2, 5, or 9, etc.

[0070] For example, the carbonate ester additive includes a cyclic carbonate ester additive and / or a linear carbonate ester additive. Furthermore, the cyclic carbonate ester additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinylethylene carbonate (VEC) and dioctyl carbonate (CC). The linear carbonate ester additive includes one or more of ethyl allyl carbonate (AEC), diphenyl carbonate (DPC), methyl allyl carbonate (MAC) and polycarbonate (VA).

[0071] For example, the sulfate additive includes a cyclic sulfonate additive and / or a hydrocarbyl sulfate additive. The cyclic sulfonate additive includes one or more of 1,3-propane sultone PS, propene sultone PES, and 3-fluoro-1,3-propane sultone FPS. The hydrocarbyl sulfate additive includes one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS.

[0072] By way of example, sulfite additives include ethylene sulfite ES and / or vinyl ethylene sulfite VES.

[0073] In some embodiments, the solid electrolyte may further include at least one of a solvent, such as acetonitrile, tetrahydrofuran, acetone, N-methylpyrrolidone, N,N-dimethylformamide, acetonitrile, tetrahydrofuran, acetone, N-methylpyrrolidone, and N,N-dimethylformamide, to enhance compatibility between the polymer matrix and the first additive, etc.

[0074] In some embodiments, the solid electrolyte may further include an auxiliary agent, such as a plasticizer, an ionic liquid, etc., to improve the ionic conductivity and lithium ion mobility of the solid electrolyte, and improve the interfacial compatibility of the electrode-electrolyte interface. Exemplarily, the plasticizer may be ethylene carbonate (EC), propylene carbonate (PC), etc.

[0075] The solid electrolyte can be prepared by uniformly mixing the polymer matrix, the first additive, etc. to form a polymer slurry, which is then applied and transferred to the surface of the electrode sheet by a solution injection method, and cured to form a film.

[0076] [Electrolyte]

[0077] The electrolyte serves to conduct metal ions between the positive electrode sheet and the negative electrode sheet. The electrolyte of the present application can be any electrolyte used in secondary batteries known in the art. The electrolyte includes a lithium salt and an organic solvent.

[0078] In some embodiments, the lithium salt is at least one selected from the group consisting of lithium hexafluoroarsenate LiPF6, lithium difluorophosphate LiPO2F2, difluorobisoxalate phosphate LiDODFP, lithium tetrafluorooxalate phosphate LiDFBP, lithium bisfluorosulfonyl imide LiFSI, lithium bistrifluoromethanesulfonyl imide LiTFSI, lithium fluorosulfonate LiSO3F, lithium nitrate LiNO3, lithium perchlorate LiClO4, lithium hexafluoroantimonate LiSbF6, and lithium hexafluoroarsenate LiAsF6. The mass percentage of the lithium salt is D2% with respect to the total mass of the electrolyte.

[0079] Furthermore, when 1≦D2≦25 and the lithium salt is within the above range, a sufficient lithium source is provided for the electrolyte to form ion passages, and the electrolyte has high ion conductivity.

[0080] Illustratively, D2 may be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 17, 19, 20, 21, 22, 23, or 25, or may be a range consisting of any two of the above numbers.

[0081] In some embodiments, the organic solvent may include a carbonate ester solvent, and the carbonate ester solvent may include a cyclic carbonate ester solvent and a chain carbonate ester solvent. By using a combination of a cyclic carbonate ester solvent and a chain carbonate ester solvent, the electrolyte has a high dielectric constant and low viscosity, and the ionic conductivity of the electrolyte can be improved. In addition, the electrochemical stability of the electrolyte is high, and the electrochemical window is significantly improved.

[0082] In some embodiments, the mass percentage of the cyclic carbonate ester solvent with respect to the total mass of the electrolyte solution is M1%, the mass percentage of the chain carbonate ester solvent with respect to the total mass of the electrolyte solution is M2%, and -3 ≦M1 / M2≦2.

[0083] When the mass percentages of the cyclic carbonate ester solvent and the chain carbonate ester solvent are within the above ranges, the ionic conductivity of the electrolyte can be further improved. Preferably, 0.1≦M1 / M2≦1, and for example, M1 / M2 may be 0.001, 0.01, 0.1, 0.2, 0.5, 0.7, 0.9, or 1, or may be a range consisting of any two of the above values.

[0084] Exemplary cyclic carbonate solvents include one or more of ethylene carbonate EC, propylene carbonate PC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinylethylene carbonate VEC, and dioctyl carbonate CC.

[0085] Furthermore, 1≦M1≦20. When the mass percentage of the cyclic carbonate ester solvent is in the above range, dissociation of lithium ions is promoted, the solubility of lithium ions is increased, and the ionic conductivity of the electrolyte can be further improved. Exemplarily, M1 may be 1, 5, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20, or may be a range consisting of any two of the above numerical values.

[0086] For example, the chain carbonate ester solvent may include one or more of ethyl allyl carbonate AEC, diphenyl carbonate DPC and methyl allyl carbonate MAC, polycarbonate VA, diethyl carbonate DEC, ethyl methyl carbonate EMC, methyl propyl carbonate MPC, ethyl propyl carbonate EPC, methyl butyl carbonate MBC, methyl acetate MA, ethyl acetate EA, methyl propionate MP and ethyl propionate EP.

[0087] Furthermore, 50≦M2≦85. When the mass percentage of the chain carbonate ester solvent is in the above range, it can provide a low viscosity to the electrolyte, which is favorable for smooth migration of lithium ions and improves the dynamic performance of the electrolyte. For example, M2 can be 50, 52, 55, 56, 58, 60, 62, 65, 66, 68 or 85.

[0088] In some embodiments, the organic solvent may further include an ether-based solvent. The ether-based solvent has a low viscosity, which can increase the ionic conductivity of the electrolyte, and the lithium ions in the electrolyte can maintain a good morphology during the circulation process. Examples of the ether-based solvent include ethyl ether, polymethoxy ether, and the like.

[0089] In some embodiments, the organic solvent may further include a nitrile-based solvent. The nitrile-based solvent has high stability, and therefore the stability of the entire electrolyte solution may be improved. Exemplarily, the nitrile-based solvent may include adiponitrile, glutaronitrile, etc.

[0090] Of course, the organic solvent may include other types of solvents, such as sulfonic solvents.

[0091] Exemplarily, the organic solvent is at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0092] In some embodiments, the electrolyte may further include an electrolyte additive. For example, the electrolyte additive may include an electrolyte film-forming additive such as an anode film-forming additive, a cathode film-forming additive, or an additive that can improve a part of the performance of the battery, such as an additive that improves the overcharge performance of the battery, or an additive that improves the high-temperature or low-temperature performance of the battery. For example, the anode film-forming additive includes one or more types of carbonate ester-based additives, sulfate ester-based additives, and sulfite ester-based additives. The specific types of electrolyte film-forming additives are as described for the solid electrolyte, and will not be described here. The mass percentage of the electrolyte film-forming additive to the total mass of the electrolyte was set to D1%.

[0093] Preferably, 10 -3 ≦D1≦10. When D1 is in the above range, it is possible to ensure that an interface film is sufficiently formed on the surface of the active material, and to improve the protective effect on the active material. Preferably, 0.1≦D1≦10. For example, D1 is 10 -3 , 10 -2 , 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, or may be a range consisting of any two of the above values.

[0094] In some embodiments, the secondary battery further satisfies 0.2≦E / (D2+D1)≦2.95, where E represents the viscosity of the electrolyte, and its unit is mPa·s.

[0095] When the secondary battery satisfies the above formula, it is advantageous to improve the dynamic performance of the electrolyte. For example, when a relatively high content of lithium salt and electrolyte film-forming additive is added, the viscosity of the electrolyte is improved, which is advantageous for cooperation between the electrolyte and the solid electrolyte, and the electrolyte film-forming additive is more likely to form a film on the active material surface through the solid electrolyte. When a chain carbonate ester solvent is added to the electrolyte, the viscosity of the electrolyte can be further controlled to be in a low range, which is advantageous for the movement of lithium ions, and the dynamic performance of the electrolyte can be ensured. Exemplarily, E / (D2+D1) may be 0.2, 0.25, 0.28, 1, 1.2, 1.5, 1.8, 2, 2.5, or 2.95, or may be a range consisting of any two of the above values.

[0096] Furthermore, 0.1≦E≦8. Exemplarily, E may be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, 6, 7, or 8, or may be a range consisting of any two of the above values. When E is in the above range, the viscosity of the electrolyte can be adjusted within an appropriate range, which is favorable for the movement of lithium ions.

[0097] [Positive electrode sheet]

[0098] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces facing each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on either one or both of the two surfaces of the positive electrode current collector.

[0099] In some embodiments, the solid electrolyte is provided on the surface of the positive electrode film layer, i.e., on the surface of the positive electrode film layer away from the positive electrode current collector, thereby providing a good protective effect for the positive electrode sheet, thereby ensuring the structural stability of the positive electrode sheet and improving the cycle performance of the secondary battery.

[0100] In some embodiments, the solid mass percentage of the solution of the solid electrolyte is m relative to the liquid mass percentage, and the compressed density of the positive electrode membrane layer is P1 g / cm 3 The thickness of the positive electrode film layer is h1 μm, and the secondary battery has a thickness of 5≦h1 * P1 / m≦250 is satisfied.

[0101] The solid matter in the solid electrolyte includes the polymer matrix, boron-containing lithium salt, etc., and the mass percentage relative to the solid electrolyte is the solid mass content of the solution of the solid electrolyte. The liquid matter in the solid electrolyte solution, such as the solvent, is the liquid mass content of the solid electrolyte relative to the mass percentage content of the solid electrolyte. The percentage of the solid mass content of the solution relative to the liquid mass content is m.

[0102] In this application, the compressed density of a material has a meaning well known in the art and can be tested by instruments and methods known in the art. For example, it can be tested by an electronic pressure tester (e.g., UTM7305 type) with reference to standard GB / T24533-2009. An exemplary test method is to weigh 1 g of the material and measure the surface area of ​​the material to be 1.327 cm2. 2 The material was placed in a mold, pressurized to 2000 kg (equivalent to 20,000 N), and held for 30 seconds, after which the pressure was released and held for 10 s. The compressed density of the material at the applied force of 20,000 N was then recorded and calculated.

[0103] When the secondary battery satisfies the above range, the polymer slurry provides good coverage for the active material and protects the interface. In this limited relationship, the diffusion path of the polymer slurry is appropriate, matches the viscosity of the polymer slurry, and is favorable for the diffusion of the polymer slurry into the active material, and matches the appropriate compression density, so that the porosity of the positive electrode membrane layer is appropriate and is favorable for the diffusion of the polymer slurry into the voids of the active material, thereby strengthening the degree of bonding between the solid electrolyte formed by the polymer slurry and the active material, and the impedance of the interface between the solid electrolyte and the active material is relatively low. Preferably, 100≦h1×P1 / m≦250. For example, h1 *P1 / m may be 0.4, 0.8, 1, 2, 3, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 100, 110, 120, 150, 160, 170, 180, 190, 200, 220, 250, 260, 280, or 300, or may be a range consisting of any two of the above values.

[0104] Additionally, 1≦m≦50. m may be 1, 2, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50, or may be a range consisting of any two of the above numbers.

[0105] Furthermore, 10≦h1≦300. h1 may be 10, 20, 50, 60, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, or a range consisting of any two of the above values.

[0106] Furthermore, 0.1≦P1≦5. P1 may be 0.1, 0.5, 1, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5, or may be a range consisting of any two of the above numbers.

[0107] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material may be a positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include at least one of a lithium transition metal oxide, a lithium-containing phosphate having an olivine structure, and a modified compound thereof. Exemplary lithium transition metal oxides may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Exemplary lithium-containing phosphates having an olivine structure may include at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and modified compounds thereof. The present application is not limited to these materials, and other materials known in the art for use as a positive electrode active material for secondary batteries may be used. These positive electrode active materials may be used alone or in combination of two or more kinds.

[0108] In some embodiments, the positive electrode active material is LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-cO2, where M and N are each independently any one selected from Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, and 0≦y≦1, 0≦x<1, 0≦z≦1, x+y+z≦1, 0≦a≦1, 0≦b≦1, 0≦c≦1, a+b+c≦1. When the positive electrode active material is used in combination with a boron-containing lithium salt, the B atom in the boron-containing lithium salt is easily bonded to the O atom in the positive electrode active material, thereby reducing the charge transfer resistance of the positive electrode active material and reducing the diffusion resistance of lithium ions in the bulk of the positive electrode active material. Therefore, when the non-aqueous electrolyte contains an appropriate content of lithium tetrafluoroborate and lithium bisfluorooxalate borate, the low cobalt or cobalt-free positive electrode active material can significantly improve the diffusion rate of lithium ions, and the lithium ions in the bulk of the low cobalt or cobalt positive electrode active material can be timely replenished to the surface, and the low cobalt or cobalt positive electrode active material can stabilize the crystal structure of the low cobalt or cobalt positive electrode active material, so as to avoid the surface of the low cobalt or cobalt positive electrode active material from excessively desorbing lithium. Since the low cobalt or cobalt-free positive electrode active material has a more stable crystal structure, it can greatly reduce the probability of problems such as the structural, chemical or electrochemical properties of the positive electrode active material becoming unstable due to lithium desorption occurring on the surface of the low cobalt or cobalt-free positive electrode active material, such as the problem of irreversible distortion and increased lattice defects of the positive electrode active material.

[0109] LiNi x Co y Mn z M 1-x-y-z O2orLiNi a Co b Al c N 1-a-b-cO2 was prepared by a common method known in the art. An exemplary preparation method is to mix a lithium source, a nickel source, a cobalt source, a manganese source, an aluminum source, an M element precursor, and an N element precursor, and sinter the mixture. The sintering atmosphere can be an oxygen-containing atmosphere, for example, an air atmosphere or an oxygen gas atmosphere. The O2 concentration of the sintering atmosphere is, for example, 70% to 100%. The sintering temperature and sintering time can be adjusted according to the actual situation.

[0110] Exemplary lithium sources include, but are not limited to, at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3), and lithium nitrate (LiNO3). Exemplary nickel sources include, but are not limited to, at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, and nickel acetate. Exemplary cobalt sources include, but are not limited to, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, and cobalt acetate. Exemplary manganese sources include, but are not limited to, at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetate. Exemplary aluminum sources include, but are not limited to, at least one of aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum oxalate, and aluminum acetate. By way of example, precursors of the M element include, but are not limited to, at least one of oxides, nitrates, carbonates, hydrogen hydroxides, and acetates of the M element. By way of example, precursors of the N element include, but are not limited to, at least one of ammonium fluoride, lithium fluoride, hydrogen fluoride, ammonium chloride, lithium chloride, hydrogen chloride, ammonium nitrate, ammonium nitrite, ammonium carbonate, ammonium hydrogen carbonate, ammonium phosphate, phosphoric acid, ammonium sulfate, ammonium hydrogen sulfate, ammonium hydrogen sulfite, ammonium sulfite, ammonium hydrogen sulfide, hydrogen sulfide, lithium sulfide, ammonium sulfide, and elemental sulfur.

[0111] In some embodiments, the molecular formula for the total mass of the positive electrode layer is LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c The mass percentage of the layered material is 80-99%. For example, the molecular formula is LiNix Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c The mass percentage of the layered material of O2 may be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, or any range therebetween. Preferably, the molecular formula is LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c The mass percentage of the O2 layered material is 85%-99%, 90%-99%, 95%-99%, 80%-98%, 85%-98%, 90%-98%, 95%-98%, 80%-97%, 85%-97%, 90%-97% or 95%-97%.

[0112] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include one or more combinations selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is 5% or less with respect to the total mass of the positive electrode film layer.

[0113] In some embodiments, the positive electrode film layer may further include a positive electrode binder. The present application does not particularly limit the type of the positive electrode binder. For example, the positive electrode binder may include one or more combinations selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene ternary copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene ternary copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the mass percentage of the positive electrode binder is 5% or less with respect to the total mass of the positive electrode film layer.

[0114] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. Examples of the metal foil sheet include aluminum foil or aluminum alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may include one or more combinations selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. The polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0115] The positive electrode membrane layer is usually formed by applying a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0116] The electrolyte of the present application can be prepared according to a conventional method in the art. For example, additives, solvents, electrolyte salts, etc. can be mixed uniformly to obtain an electrolyte. The order of addition of each material is not particularly limited. For example, additives, electrolyte salts, etc. can be added to a non-aqueous solvent and mixed uniformly to obtain a non-aqueous electrolyte.

[0117] In the present application, each component and its content in the electrolyte solution can be measured according to a method known in the art, for example, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0118] In the electrolyte test of the present application, a freshly prepared electrolyte may be taken out as it is, or the electrolyte may be taken out from a secondary battery. One exemplary method for taking an electrolyte from a secondary battery is to discharge the secondary battery to the discharge end voltage (for safety, the battery is generally put into a fully discharged state) and then centrifugal treatment, and the appropriate amount of liquid obtained from the centrifugal treatment is the nonaqueous electrolyte. The nonaqueous electrolyte may be taken directly from the electrolyte inlet of the secondary battery.

[0119] [Negative electrode sheet]

[0120] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0121] For example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.

[0122] In some embodiments, the solid electrolyte is provided on the surface of the negative electrode film layer, i.e., the surface of the negative electrode film layer away from the negative electrode current collector, and provides good protection for the negative electrode sheet, thereby ensuring the structural stability of the negative electrode sheet and improving the cycle performance of the secondary battery.

[0123] In some embodiments, the percentage of the solid mass content of the solid electrolyte solution relative to the liquid mass content is m, and the compressed density of the negative electrode membrane layer at an applied force of 20,000 N is P2g / cm 3 The thickness of the negative electrode film layer is h2 μm, and the secondary battery satisfies 25≦h2×P2 / m≦245.

[0124] When the secondary battery satisfies the above range, the polymer slurry has a good coating on the active material, matches the viscosity of the polymer slurry, is favorable for the polymer slurry to diffuse into the active material, and matches the appropriate compression density, so that the porosity of the negative electrode film layer is appropriate, and is favorable for the polymer slurry to diffuse into the voids of the active material, so that the degree of bonding between the solid electrolyte formed by the polymer slurry and the active material is strong, and the impedance of the interface between the solid electrolyte and the active material is relatively low. Preferably, 50≦h2*P2 / m≦200. For example, h2 * P2 / m may be 0.04, 0.08, 0.1, 0.2, 0.3, 0.4, 0.8, 1, 2, 3, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 100, 110, 120, 150, 160, 170, 180, 190, or 200, or may be a range consisting of any two of the above values.

[0125] Additionally, 1≦m≦50. m can be 1, 2, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50, or a range consisting of any two of the foregoing values.

[0126] Furthermore, 10≦h2≦300. h2 may be 10, 20, 50, 60, 80, 100, 120, 150, 180, 200, 220, 250, 280, 300, or a range consisting of any two of the above values.

[0127] Furthermore, 1≦P2≦5. P2 may be 1, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, or 5, or may be a range consisting of any two of the above numbers.

[0128] In some embodiments, the negative electrode active material may be a battery negative electrode active material known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, lithium titanate, and lithium aluminum alloy. The silicon-based material may be at least one selected from elemental silicon, silicon oxygen compound, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material is at least one selected from elemental tin, tin oxygen compound, and tin alloy. However, the present application is not limited to these materials, and other materials used as battery negative electrode active materials may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0129] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. For example, the negative electrode binder may include one or more combinations selected from styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-soluble acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PSMA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is 5% or less with respect to the total mass of the negative electrode film layer.

[0130] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include one or more combinations selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is 5% or less with respect to the total mass of the negative electrode film layer.

[0131] In some embodiments, the negative electrode membrane layer may further include other additives. For example, the other additives may include thickeners such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, the mass percentage of the other additives is 2% or less, based on the total mass of the negative electrode membrane layer.

[0132] In some embodiments, the negative electrode current collector may be a metal foil piece or a composite current collector. Examples of the metal foil include copper foil and copper alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may include one or more combinations selected from copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. The polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0133] The negative electrode membrane layer is usually formed by applying a negative electrode slurry to a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and optional other auxiliary agents in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0134] The negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet further includes a protective layer covering the surface of the negative electrode film layer.

[0135] In the present application, the mass percentage of a substance can be measured according to a method known in the art, for example, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0136] [Separator]

[0137] In some embodiments, the secondary battery further includes a separator. The type of the separator in the present application is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.

[0138] In some embodiments, the separator is made of at least one material selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of the layers may be the same or different, and are not particularly limited.

[0139] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly by a winding or lamination process.

[0140] In some embodiments, the secondary battery may include an exterior case that is used to seal the electrode assembly and electrolyte.

[0141] In some embodiments, the exterior of the secondary battery may be a hard case such as a hard plastic case, an aluminum case, or a steel case. The exterior of the secondary battery may be a soft bag, such as a bag soft bag. The material of the soft package may be plastic. Examples of plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0142] The shape of the secondary battery of the present application is not particularly limited, and may be cylindrical, rectangular, or any other shape. Figure 1 shows an example of a secondary battery 5 having a rectangular structure.

[0143] In some embodiments, as shown in FIG. 1 and FIG. 2, the exterior may include a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are surrounded to form a chamber. The case 51 has an opening communicating with the chamber, and the cover plate 53 closes the opening to close the chamber. The positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is sealed in the chamber. The electrolyte is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one type or multiple types, and may be adjusted according to requirements.

[0144] The method for manufacturing the secondary battery of the present application is known. In some embodiments, a secondary battery can be formed by assembling a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. For example, a positive electrode sheet, a separator, and a negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process, and the electrode assembly can be placed in an outer casing, dried, and then an electrolyte can be injected, and a secondary battery can be obtained through processes such as vacuum sealing, standing, chemical formation, and shaping.

[0145] In some embodiments of the present application, the secondary battery of the present application may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0146] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastener.

[0147] Preferably, the battery module 4 further includes a housing having an accommodation space, and the multiple secondary batteries 5 are accommodated in the accommodation space.

[0148] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0149] 4 and 5 are schematic diagrams of a battery pack 1 as an example. As shown in Fig. 4 and 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 covers the lower housing 3 to form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0150] power consumption equipment

[0151] According to a second aspect, the present application provides a power consumption device, which includes at least one of the secondary batteries, battery modules, and battery packs of the present application. The secondary batteries, battery modules, and battery packs may be used as power sources for the power consumption device, or may be used as energy storage means for the power consumption device. The power consumption device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, and a satellite, an energy storage system, etc.

[0152] The power consuming device can select the secondary battery, the battery module or the battery pack according to its needs.

[0153] 6 is a schematic diagram of an example power consuming device 6, which may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. A battery pack 1 or a battery module may be employed to meet the high power and high energy density requirements of the power consuming device.

[0154] As another example, the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. This power consuming device is usually required to be thin and may employ a secondary battery as a power source.

[0155] Working Example

[0156] The following examples are provided to more specifically describe the contents of the present application, but these examples are merely illustrative, and it will be apparent to those skilled in the art that various modifications and changes may be made within the scope of the disclosure of the present application. All parts, percentages, and ratios reported in the following examples are based on mass unless otherwise specified. All reagents used in the examples are commercially available or may be synthesized according to conventional methods. They can be used as they are without further processing. All devices used in the examples are commercially available.

[0157] Example 1

[0158] 1. Manufacturing of positive electrode sheets

[0159] As the positive electrode current collector, an aluminum foil having a thickness of 12 μm was used.

[0160] Positive electrode active material LiNi 0.6 Co 0.2 Mn2O2, carbon black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder were thoroughly mixed in a weight ratio of 97.5:1.4:1.1 in an appropriate amount of NMP solvent and stirred to form a uniform positive electrode slurry. The positive electrode slurry was then uniformly applied to the surface of an aluminum foil as a positive electrode current collector, and after drying and cold pressing, a positive electrode film layer was obtained.

[0161] The polymer matrix P (VDF-HFP), boron-containing lithium salt (LiBOB), and lithium salt LiTFSI were uniformly stirred to form a polymer slurry, which was then vacuum degassed. The solution was then poured onto the positive electrode film layer and left for 12 hours at 5°C to 35°C and in a humidity environment of 0.1% to 30%, causing a phase transition and hardening to form a solid electrolyte.

[0162] 2. Manufacturing of negative electrode sheets

[0163] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0164] The negative electrode active material graphite, the binder styrene butadiene rubber (SBR), the thickener sodium carboxymethylcellulose (CMC-Na), and the conductive agent carbon black (SuperP) were thoroughly mixed in a weight ratio of 96.2:1.8:1.2:0.8 in an appropriate amount of deionized water solvent to form a uniform negative electrode slurry. The negative electrode slurry was then uniformly applied to the surface of the copper foil, which was the negative electrode current collector, and dried and cold pressed to obtain a negative electrode film layer.

[0165] The polymer matrix P (VDF-HFP), boron-containing lithium salt (LiBF4), and lithium salt LiTFSI were degassed under vacuum, then coated onto the negative electrode film layer and left for 12 hours at 5°C to 35°C and a humidity of 0.1% to 30%, to harden and form a solid electrolyte.

[0166] 3. Separator

[0167] A porous polyethylene (PE) film was used as the separator.

[0168] 4. Electrolyte production

[0169] In an environment with a water content of less than 10 ppm, nonaqueous organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then lithium salt was dissolved in the mixed solvent to obtain an electrolyte with a lithium salt concentration of 1 mol / L.

[0170] 5. Manufacturing of secondary batteries

[0171] The positive electrode sheet, separator, and negative electrode sheet are laminated in this order, and the separator is made to act as a separator between the positive electrode sheet and the negative electrode sheet. After that, the laminate is wound to obtain an electrode assembly. The electrode assembly is placed in an outer can and dried, after which an electrolyte is injected, and the assembly is subjected to processes such as vacuum sealing, standing, chemical formation, and shaping to obtain a lithium ion battery.

[0172] Example 2

[0173] The secondary batteries of Examples 2-1 to 2-12 were manufactured by a method similar to that of Example 1. The difference from Example 1 is that Examples 2-1 to 2-12 adjusted the mass percentages of the first additive and the polymer matrix.

[0174] Comparative Example 1 and Comparative Example 2

[0175] The secondary batteries of Comparative Example 1 and Comparative Example 2 were manufactured in a similar manner to that of Example 1. The difference from Example 1 is that Comparative Example 1 and Comparative Example 2 adjusted the mass percentage of the first additive and the polymer matrix. The data of Example 1, Example 2, and Comparative Example are shown in Table 1. vinegar.

[0176] [Table 1]

[0177] Example 3

[0178] The secondary batteries of Examples 3-1 to 3-5 were manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the mass percentage B1% of the boron-containing lithium salt was adjusted in Examples 3-1 to 3-5. The data of Examples 1 and 3 are shown in Table 2.

[0179] [Table 2]

[0180] Example 4

[0181] The secondary batteries of Examples 4-1 to 4-7 were manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the mass percentage D1% of the electrolyte film-forming additive was adjusted in Examples 4-1 to 4-7. The data of Examples 1 and 4 are shown in Table 3.

[0182] [Table 3]

[0183] Example 5

[0184] The secondary batteries of Examples 5-1 to 5-8 were manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the parameters of Examples 5-1 to 5-8, such as the compressed density P1 of the positive electrode film layer, were adjusted. The data of Examples 1 and 5 are shown in Table 4.

[0185] [Table 4]

[0186] Example 6

[0187] The secondary batteries of Examples 6-1 to 6-6 were manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the parameters of Examples 6-1 to 6-6, such as the compressed density P2 of the negative electrode film layer, were adjusted. The data of Examples 6-1 to 6-6 are shown in Table 5.

[0188] [Table 5]

[0189] Test Part

[0190] 1. Testing parameters of positive and negative electrode sheets

[0191] 1.1 Positive / negative electrode film thickness test

[0192] Use a ladybug sand micrometer to measure the thickness of the positive electrode sheet at at least 12 different positions along the thickness direction of the positive electrode sheet, and the average value is taken as the thickness h1 of the positive electrode sheet, from which the thickness of the positive electrode current collector is subtracted to obtain the thickness of the positive electrode film layer.

[0193] Use a ladybug sand micrometer to measure the thickness of the negative electrode sheet at at least 12 different positions along the thickness direction of the negative electrode sheet, and the average value is taken as the thickness h2 of the negative electrode sheet, from which the thickness of the negative electrode current collector is subtracted to obtain the thickness of the negative electrode film layer.

[0194] 1.2 Testing the Compressed Density P of Positive / Negative Film Layers

[0195] A certain amount of the negative active material sample was taken and placed in a mold with a base area of ​​1.327 cm2 of a UTM7305 type electronic pressure tester, pressurized to 2000 kg (equivalent to 20,000 N), held for 30 seconds, released, and held for 10 seconds, and the compressed density of the powder of the negative active material at an applied force of 20,000 N was recorded and calculated. The test standard was in accordance with GB / T24533-2009.

[0196] A certain amount of the positive active material sample prepared above was taken and placed in a mold with a base area of ​​1.327 cm2 of a UTM7305 type electronic pressure tester, pressurized to 2000 kg (equivalent to 20,000 N), held for 30 seconds, then released and held for 10 seconds, after which the powder compression density of the positive active material at an applied force of 20,000 N was recorded and calculated. The test standard was in accordance with GB / T24533-2009.

[0197] 2. Electrolyte viscosity test

[0198] After taking an appropriate amount of electrolyte sample and cleaning the sample cup and rotor in order, take an appropriate amount of electrolyte and place it in the sample cup, keep the temperature constant at 25℃, and measure the viscosity of the DV-2TLV (the formula is FSR=TK * SMC * 10000 / RPM), fixed the electrolyte and organic solvent, selected 18# rotor, 70r / min rotation speed, selected Multi Point Average data collection mode, automatically recorded and detected. The test standard was in accordance with GB / T10247-2008.

[0199] 3. Secondary battery performance testing

[0200] 3.1 Testing the cycle performance of secondary batteries

[0201] (1) Testing the room temperature cycle performance of secondary batteries

[0202] At 25°C, the secondary battery was charged to 4.4V at a constant current of 1C, and continued to be charged at a constant voltage until the current became 0.05C. At this time, the secondary battery was in a fully charged state, and the charge capacity at this time was recorded, that is, the charge capacity of the first cycle. After leaving the secondary battery to stand for 5 minutes, it was discharged to 2.8V at a constant current of 1C, which is one cycle of charge and discharge, and the discharge capacity at this time was recorded, that is, the discharge capacity of the first cycle. The secondary battery was subjected to a cycle charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded. Capacity retention rate (%) of the secondary battery after 600 cycles at 25°C = discharge capacity after 600 cycles / discharge capacity at the first cycle × 100%.

[0203] 3.2 Secondary battery safety performance testing

[0204] At 25°C, the secondary battery is charged to 4.3V at a constant current of 1C, and charging is continued at a constant voltage until the current becomes 0.05C, at which point the secondary battery is fully charged. The fully charged secondary battery is placed in a well-sealed high-temperature box, heated to 100°C at 5°C / min, held for 1 hour, then heated to 105°C at 5°C / min, held for 30 minutes, and then held for 30 minutes for every 5°C increase at a heating rate of 5°C / min, until the secondary battery expires. The maximum temperature T max The record was . max The higher the thermal box safety performance of the secondary battery, the better.

[0205] In order to ensure the reliability of the test results, each of the above tests should be performed using at least three parallel samples, and the average value should be used as the test result.

[0206] 3.3 Testing DC resistance (DCR) of secondary battery cells

[0207] 25℃, DCR test: First, a capacity test was performed. The specific operating procedure was as follows: the secondary battery was left to stand at 25℃ for 2 hours using a constant current charge / discharge tester, charged to 4.4V at a rate of 0.33C, and then charged at a constant voltage until the current became less than 0.05C. After leaving the battery to stand for 5 minutes, it was discharged to 2.8V. The discharge capacity at this time was recorded and used as the initial capacity of the secondary battery. Then, adjust the battery remaining capacity (expressed as SOC, the formula is battery remaining capacity / initial capacity×100%), and perform the test DCR. First, fully charge the battery to 4.4V at 0.33C, charge to 4.4V at a constant voltage until the current is less than 0.05C, then fully discharge at 0.05C for 1h, and discharge at a constant current to adjust the secondary battery to 50% SOC. At this time, the voltage of the secondary battery is U1, and the secondary battery is discharged at a constant current of 4C I1 for 30 seconds, sampling is adopted for 0.1 seconds, and the discharge end voltage is U2. The discharge DC internal resistance of the secondary battery at 50% SOC represents the initial DC internal resistance of the secondary battery, and the initial DC internal resistance of the secondary battery (mΩ)=(U1-U2) / I1.

[0208] Test results

[0209] The present application shows in Tables 6 to 10 the effects of improving the cycle performance, safety performance and dynamic performance of the secondary battery.

[0210] [Table 6]

[0211] As can be seen from Table 6, the safety performance of the secondary battery is improved by attaching the solid electrolyte to the electrode sheet, but the kinetics of the interfacial transmission of lithium ions is poor and the interfacial impedance is large, as can be seen from Comparative Example 1 and Comparative Example 2. In Examples 1 to 2-12, the mass percentage of the polymer matrix and the first additive in the solid electrolyte is controlled within an appropriate range, for example, 0.1≦B / A≦19, preferably 0.5≦B / A≦10, thereby significantly improving the impedance of the secondary battery, improving its kinetic performance, and also improving the cycle performance and safety performance of the secondary battery.

[0212] [Table 7]

[0213] As can be seen from Table 7, the performance of the secondary battery can be adjusted by adjusting the mass percentage ratio of the boron-containing lithium salt in the first additive and the negative electrode film-forming additive, especially when 0.002≦B1 / B2≦10, the cycle performance and kinetic performance of the secondary battery are obviously improved.

[0214] [Table 8]

[0215] As can be seen from Table 8, the performance of the secondary battery can be adjusted by adjusting the correlation between the mass percentage of the electrolyte film-forming additive and the lithium salt in the electrolyte and the viscosity of the electrolyte. In particular, when 0.2≦E / (D1+D2)≦2.95, the cycle performance and kinetic performance of the secondary battery are significantly improved.

[0216] [Table 9]

[0217] As can be seen from Table 9, by adjusting the correlation between the positive electrode film layer and the solid electrolyte, the protective power of the solid electrolyte against the positive electrode film layer can be adjusted to adjust the performance of the secondary battery, especially when 5≦h1 * P1 / m≦250, preferably 70≦h1 * When P1 / m≦250, the cycle performance and kinetic performance of the secondary battery are obviously improved.

[0218] [Table 10]

[0219] As can be seen from Table 10, the performance of the secondary battery can be adjusted by adjusting the correlation between the negative electrode film layer and the solid electrolyte, and by adjusting the protective power of the solid electrolyte against the negative electrode film layer. In particular, 5≦h1 * P1 / m≦250, preferably 25≦h2 * When P2 / m≦245, the cycle performance and kinetic performance of the secondary battery are obviously improved.

[0220] Although the present application has been described above with reference to the preferred embodiments, various improvements may be made without departing from the scope of the present application, and some of the components may be replaced with equivalents. In particular, as long as there is no structural contradiction, the technical features mentioned in each embodiment may be arbitrarily combined. The present application is not limited to the specific embodiments disclosed above, but includes all aspects included in the scope of the claims.

Claims

1. A secondary battery, a positive electrode sheet including a positive electrode film layer; a negative electrode sheet including a negative electrode film layer; An electrolyte; a solid electrolyte provided on a surface of the positive electrode film layer and / or the negative electrode film layer, the solid electrolyte including a polymer matrix and a first additive, the first additive being arranged to form an interfacial film on the surface of the positive electrode film layer and / or the negative electrode film layer; The mass percentage of the polymer matrix with respect to the total mass of the solid electrolyte is A %, The mass percentage of the first additive with respect to the total mass of the solid electrolyte is B%, The secondary battery satisfies 0.1≦B / A≦19, preferably 0.5≦B / A≦10.

2. The secondary battery according to claim 1 , wherein the secondary battery satisfies 5≦A≦99 and / or 0.1≦B≦95.

3. The first additive is A boron-containing lithium salt having a mass percentage of B1% relative to the total mass of the solid electrolyte; a negative electrode film-forming additive having a mass percentage of B2% relative to the total mass of the solid electrolyte; The secondary battery according to claim 1 , wherein the secondary battery satisfies 0.002≦B1 / B2≦10.

4. The secondary battery according to claim 3 , wherein the secondary battery satisfies 0.1≦B1≦50 and / or 0.1≦B2≦50.

5. The molecular formula of the boron-containing lithium salt is LiBF a O b C c P d In the molecular formula, 0≦a≦4, 0≦b≦8, 0≦c≦4, and 0≦d≦4. Preferably, the boron-containing lithium salt is lithium tetrafluoroborate LiBF 4 5. The secondary battery according to claim 3, comprising one or more of lithium bis(oxalato)borate (LiBOB) and lithium bis(fluorooxalato)borate (LiDFOB).

6. The secondary battery according to claim 3 , wherein the negative electrode film-forming additive comprises one or more of a carbonate-based additive, a sulfate-based additive, and a sulfite-based additive.

7. The carbonate ester-based additive includes a cyclic carbonate ester solvent and / or a chain carbonate ester solvent, and preferably, the cyclic carbonate ester solvent includes one or more of vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinylethylene carbonate VEC, and dioctyl carbonate CC, and the chain carbonate ester solvent includes one or more of ethyl allyl carbonate AEC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA, and / or The sulfate additive includes a cyclic sulfonate additive and / or a hydrocarbon sulfate additive, and preferably, the cyclic sulfonate additive includes one or more of 1,3-propane sultone PS, propene sultone PES, and 3-fluoro-1,3-propane sultone FPS, and / or the hydrocarbon sulfate additive includes one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS, and / or The secondary battery according to claim 6 , wherein the sulfite ester additive comprises ethylene sulfite ES and / or vinyl ethylene sulfite VES.

8. The electrolyte solution is A cyclic carbonate solvent having a mass percentage of M1% relative to the total mass of the electrolyte; A chain carbonate ester solvent having a mass percentage of M2% relative to the total mass of the electrolyte solution; The secondary battery is 10 -3 ≦M1 / M2≦2, with a preferred range of 0.1≦M1 / M2≦1; The secondary battery according to claim 1 , wherein 1≦M1≦20 and / or 50≦M2≦85.

9. The cyclic carbonate solvent comprises one or more of ethylene carbonate EC, propylene carbonate PC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinylethylene carbonate VEC and dioctyl carbonate CC, and / or The secondary battery according to claim 8, wherein the chain carbonate ester solvent includes one or more of ethyl allyl carbonate AEC, diphenyl carbonate DPC and methyl allyl carbonate MAC, polycarbonate VA, diethyl carbonate DEC, ethyl methyl carbonate EMC, methyl propyl carbonate MPC, ethyl propyl carbonate EPC, methyl butyl carbonate MBC, methyl acetate MA, ethyl acetate EA, methyl propionate MP, and ethyl propionate EP.

10. The electrolyte solution is An electrolyte film-forming additive having a mass percentage of D1% relative to the total mass of the electrolyte; A lithium salt having a mass percentage of D2% relative to the total mass of the electrolyte solution; 10. The secondary battery according to claim 1, wherein the secondary battery satisfies 0.2≦E / (D1+D2)≦2.95, in which E represents the viscosity of the electrolyte and its unit is mPa·s.

11. The percentage of the solid mass content of the solid electrolyte solution relative to the liquid mass content is m; The compressed density of the positive electrode film layer is P1g / cm 3 year, The thickness of the positive electrode film layer is h 1 μm. The secondary battery has a temperature of 5≦h1 * The secondary battery according to claim 1 , wherein P1 / m≦250 is satisfied.

12. The percentage of the solid mass content of the solid electrolyte solution relative to the liquid mass content is m; The compressed density of the negative electrode film layer is P2g / cm 3 year, The thickness of the negative electrode film layer is h2 μm. The secondary battery has a temperature of 25≦h2 * The secondary battery according to claim 1 , wherein P2 / m≦245 is satisfied.

13. A battery module comprising the secondary battery according to claim 1 .

14. A battery pack comprising the battery module according to claim 13.

15. A power consuming device comprising: the secondary battery according to claim 1 ; the battery module according to claim 13 ; or the battery pack according to claim 14 .

Citation Information

Patent Citations

  • Method for prefabricating SEI film on surface of metal lithium negative electrode

    CN111599990A

  • Electrode pole piece and lithium ion secondary battery containing same

    CN111933944A

  • Modified active material for semi-solid battery and preparation method and application thereof

    CN113690418A

  • Negative electrode for lithium secondary battery, and lithium secondary battery containing the same

    JP2009135104A

  • Method for manufacturing nonaqueous electrolyte secondary battery

    WO2013076847A1